2011
DOI: 10.1127/0077-7749/2011/0162
|View full text |Cite
|
Sign up to set email alerts
|

The decapod crustaceans of the Upper Jurassic Solnhofen Limestones: A historical review and some recent discoveries

Abstract: The Solnhofen Limestones represent one of the most important sources for crustacean diversity in the Jurassic and even for their fossil record in the Mesozoic. A brief overview of the history of science since the beginning of 18th century and the circumstances of the fossil recoveries are provided. The fossils come from various localities of slightly different ages (late Kimmeridgian-early Tithonian). Most specimens did not live at their later places of burial, but were swept in as exuviae from more or less di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Although no conclusive evidence was provided, Nybelin (1958) suggested that the fish Thrissops formosus may have fed on pelagic crustaceans in southern Germany during the Late Jurassic. Decapods are well known from these lithographic limestones (e.g., Garassino and Schweigert, 2006;Schweigert, 2011). Another example from the Jurassic are Sinemurian fragments of crustacean carapaces in the alimentary tract of the thylacocephalan crustacean Ostenocaris cypriformis from Italy (Pinna et al, 1985).…”
Section: Predation Of Crustaceansmentioning
confidence: 99%
“…Although no conclusive evidence was provided, Nybelin (1958) suggested that the fish Thrissops formosus may have fed on pelagic crustaceans in southern Germany during the Late Jurassic. Decapods are well known from these lithographic limestones (e.g., Garassino and Schweigert, 2006;Schweigert, 2011). Another example from the Jurassic are Sinemurian fragments of crustacean carapaces in the alimentary tract of the thylacocephalan crustacean Ostenocaris cypriformis from Italy (Pinna et al, 1985).…”
Section: Predation Of Crustaceansmentioning
confidence: 99%
“…[ 32 ]) and analyses of its exceptionally preserved fossils. Studies of Solnhofen fossils using UV include those of decapod crustaceans [ 33 35 ], ammonites [ 36 , 37 ], fish [ 38 , 39 ], pterosaurs [ 40 , 41 ] and dinosaurs [ 42 46 ] among others. In recent years, laser light of 405–532 nm wavelengths has been applied to fossils to induce fluorescence and reveal clearer and/or otherwise unseen details [ 1 , 47 ], especially on soft-tissue bearing fossils pertinent to the study of avian and flight origins and integument evolution [ 1 , 3 5 , 8 – 13 , 15 , 16 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of UV fluorescence in analysing fossils from the Solnhofen limestones in the early twentieth century [31], the technique has been increasingly used in the search for (sensu Croft et al [32]) and analyses of its exceptionally preserved fossils. Studies of Solnhofen fossils using UV include those of decapod crustaceans [33][34][35], ammonites [36,37], fish [38,39], pterosaurs [40,41] and dinosaurs [42][43][44][45][46] among others. In recent years, laser light of 405-532 nm wavelengths has been applied to fossils to induce fluorescence and reveal clearer and/or otherwise unseen details [1,47], especially on soft-tissue bearing fossils pertinent to the study of avian and flight origins and integument evolution [1,[3][4][5][8][9][10][11][12][13]15,16,48,49].…”
mentioning
confidence: 99%
“…The lithographic limestones of Southern Germany have yielded especially numerous representatives of Decapoda (Oppel 1862;Schweigert & Garassino 2004;Garassino & Schweigert 2006;Schweigert 2011Schweigert , 2015Schweigert et al 2016), but also several representatives of Stomatopoda (Haug et al 2009a(Haug et al , 2010. This also includes spectacularly well-preserved larval forms of both groups, only known from very few other localities.…”
mentioning
confidence: 99%